2020
DOI: 10.21315/aamj2020.25.1.6
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Millennials Happy in their Workplace?

Abstract: Happiness in the workplace remains to be an under-researched field which is unfortunate considering that the happiness-productive worker link has been strongly established. More essentially, there has been a lack of research on happiness in the workplace which considers a specific sample of millennials. In preparation for a workforce dominated with millennials, this research will help address the gap with regards to the lack of research on Malaysian millennials’ happiness in the workplace. Through a thorough l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…The most common ways of operationalising the construct of happiness mentioned in HPW's thesis have been: affections [5,25,28,29,36], well-being [20, 29,33,35,48,49], subjective or psychological well-being [4,20,22,30,35,37,48,49], happiness [16,37,45,50] and satisfaction, both with life and at a professional level [4,5,20,21,25,28,29,33,35,36,45,50,51]. However, there are also others such as motivations [50,52], organisational commitment [50], and engagement [36,50].…”
Section: Happiness At Workmentioning
confidence: 99%
“…The most common ways of operationalising the construct of happiness mentioned in HPW's thesis have been: affections [5,25,28,29,36], well-being [20, 29,33,35,48,49], subjective or psychological well-being [4,20,22,30,35,37,48,49], happiness [16,37,45,50] and satisfaction, both with life and at a professional level [4,5,20,21,25,28,29,33,35,36,45,50,51]. However, there are also others such as motivations [50,52], organisational commitment [50], and engagement [36,50].…”
Section: Happiness At Workmentioning
confidence: 99%
“…Friendships at work may allow millennial employees to have more positive experiences in the workplace, thereby leading to increased AWB and happiness. Further, Yap and Badri (2020) have also argued that workplace friendships might hold higher importance to millennials, as this generation could view relationships at work as an extension of their family, as opposed to boomers who might perceive work relationships as merely transactional. A possibility for this could be due to millennials having a higher likelihood to be still single as compared to boomers (Yap and Badri, 2020), which increases the possibility of them seeking for connections and friendships at work.…”
Section: The Mediating Role Of Friendships At Workmentioning
confidence: 99%
“…As a unique individual resource, various scholars have highlighted the unique psychological benefits associated with the emotional and social functions of friendships in the workplace. Yap and Badri (2020) found that friendships at work promoted AWB among millennials. Accordingly, we expect that millennial workers’ feelings of gratitude in the workplace will influence their friendships at work, which, in turn, will influence their well-being and happiness.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…'Quality of work life' and 'workplace happiness' are proven and known to have a positive relationship (Rasli, et al, 2017). Yap and Badri (2020) in their study have found that the working environment is one of the main antecedents to employee job happiness. In other works, by Jamal and Budke (2020) suggested that organizational culture, which is assumed to be part of the working environment, can also foster job happiness among employees.…”
Section: Introductionmentioning
confidence: 96%